IDENTIFIKASI Listeria spp. PADA PANGAN JAJANAN BERBASIS IKAN DI KOTA BOGOR - Elia Yuswita; Siti Nurjanah; Winiati P. Rahayu (Jurnal Teknologi dan Industri Pangan, 2016)
L. monocytogenes contamination in processed food, especially fish-based snack, may results from contaminated raw materials, underprocessed or recontamination. The aims of this study were to identify the presence of Listeria spp. especially L. monocytogenes by PCR method and biochemical methods, as well as calculate the prevalence of Listeria spp. in fish-based snack food in Bogor. This study was conducted of 4 steps: (1) determination of L. monocytogenes’s DNA limit detection, (2) sample preparation, (3) identification of L. monocytogenes with real-time PCR, and (4) identification of Listeria spp. with biochemical methods. The results showed that DNA detection limits of L. monocytogenes in fish meatball and otak-otak were at 8.3x102 and 2.9x102 CFU/g,  respectively. The study on 65 samples indicated that contamination of L. monocytogenes was not observed, but other species of Listeria spp., namely L. grayi and L. innocua, were found. The prevalence of L. grayi and L. innocua in siomay was at 5.9%, while the prevalence of L. grayi in shrimp meatballs, fish meat balls, fried meatballs was at 8.3, 9.1, and 50%, respectively. Furthermore, L. innocua from takoyaki samples with a prevalence of 20% was observed.